Construction and development of Traditional Chinese Medicine nursing clinics (中医护理门诊建设和发展思路与方法) - FA Hua (樊华); YANG Jianying (杨剑英) (中西医结合护理)
This paper summarized the construction experience of the Traditional Chinese Medicine nursing clinics and discussed the thought of future development. Surgery was conducted to investigate the patients’ need of healthcare service form Traditional Chinese Medicine nursing clinics, and outpatient service with characteristic of Traditional Chinese Medicine was established; A group of certified clinic nurses were recruited, and training and Learning plan was made to improve their professional competence of Traditional Chinese Medicine nursing; outpatient process and appraisal mechanism was developed for the continuous quality improvement; interventions were carried out to improve nursing service capacity and patient’s satisfaction. The construction and development of Traditional Chinese Medicine nursing clinics have met the needs of patients, and its shortcomings in the process of operation need to be improved, for the future development of outpatient service with characteristic of Traditional Chinese Medicine. (通过总结中医护理门诊的建设经验, 探讨中医护理门诊建设和发展的思路与方法。通过前期调研分析中医护理门诊的需求, 制定具有中医特色的护理门诊服务内容; 成立中医护理门诊小组, 确定中医护理门诊人员资质, 通过有计划地学习、参观、培训, 培养中医护理门诊人员才能; 按照制定的计划优化中医护理门诊流程, 制定考核机制, 从而在运行过程中持续质量改进; 满足患者就诊需求, 提升中医护理服务能力和患者满意度; 总结中医护理门诊工作, 结合现代中医门诊实践, 不断完善和丰富护理学的内容。中医护理门诊的建设和发展更符合患者需求, 但中医博大精深, 开展过程中仍然可能存在一些问题, 需要不断改进完善, 从而积极发展具有中医特色的门诊服务。)